2011
DOI: 10.1111/j.1750-3841.2011.02282.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Acid Composition and Antioxidant Properties of Malaysian Honeys

Abstract: The phenolic acid and flavonoid contents of Malaysian Tualang, Gelam, and Borneo tropical honeys were compared to those of Manuka honey. Ferric reducing/antioxidant power assay (FRAP) and the 1,1-diphenyl-2-picryl-hydrazyl (DPPH) radical-scavenging activities were also quantified. All honey extracts exhibited high phenolic contents (15.21 ± 0.51- 42.23 ± 0.64 mg/kg), flavonoid contents (11.52 ± 0.27- 25.31 ± 0.37 mg/kg), FRAP values (892.15 ± 4.97- 363.38 ± 10.57 μM Fe[II]/kg), and high IC₅₀ of DPPH radical-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
206
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(246 citation statements)
references
References 35 publications
14
206
6
1
Order By: Relevance
“…Despite accumulating evidence suggesting the potential of honeys in combating colorectal cancer, there is not much evidence regarding local Gelam honey having anticancer effect and especially colon cancer in particular. There might be differences in the anti-cancer property attributed to differences in the composition of biochemical constituents between different types of honeys (Gheldof et al, 2002;Khalil et al, 2011;Chua et al, 2013). The work documented here is an extension to our previous work in colon adenocarcinoma cell line HT 29 where, we found that Gelam honey exhibited higher chemopreventative effects on HT 29 colon cancer cell line than Nenas honey by inducing apopotosis and suppressing inflammation possibly through its antioxidant property (Wen et al, 2012).…”
Section: Discussionsupporting
confidence: 70%
“…Despite accumulating evidence suggesting the potential of honeys in combating colorectal cancer, there is not much evidence regarding local Gelam honey having anticancer effect and especially colon cancer in particular. There might be differences in the anti-cancer property attributed to differences in the composition of biochemical constituents between different types of honeys (Gheldof et al, 2002;Khalil et al, 2011;Chua et al, 2013). The work documented here is an extension to our previous work in colon adenocarcinoma cell line HT 29 where, we found that Gelam honey exhibited higher chemopreventative effects on HT 29 colon cancer cell line than Nenas honey by inducing apopotosis and suppressing inflammation possibly through its antioxidant property (Wen et al, 2012).…”
Section: Discussionsupporting
confidence: 70%
“…The main constituents of honey are carbohydrates such as monosaccharides, disaccharides, oligosaccharides, and polysaccharides as well as enzymes such as glucose oxidase, diastase, invertase, catalase, and peroxidase. Other chemical contents of honey are organic acid, ascorbic acid, vitamins, amino acids, flavonoids and phenolic acids [38]. Malaysian Tualang honey which has been used in our study is known for its antimicrobial, antiparasitic, antioxidant, and antiinflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed the potential of Tualang honey in improving the memory of young and aged rats. It is assumed that the improvement of memory by Tualang honey is due to its antioxidant capacity attributed to the flavonoids contents [29,[55][56][57]. Other types of antioxidants present in honey include enzymatic (e.g.…”
Section: Discussionmentioning
confidence: 99%